A 25-Year Perspective on Logic Programming Achievements of the Italian Association for Logic Programming, GULP - Dovier, Agostino.; Pontelli, Enrico. (Lecture Notes in Computer Science, 2010)
This book celebrates the 25th anniversary of GULPthe Italian Association for Logic Programming. Authored by Italian researchers at the leading edge of their fields, it presents a state-of-the-art survey of logic programming, making it a useful reference for both researchers and students. The volume contains 14 invited papers, each giving a detailed analysis of a specific field of logic programming and providing both a historical perspective and a precise discussion of current research. The book closes with a chapter reviewing in detail the main applications of logic programming developed in Italian researchers in the last 25 years, illustrating successful work done and potential directions for future developments.